Inter-hospital 'patient expect' calls of clinical handovers for expected patients transferred from rural to metropolitan hospitals: A retrospective clinical audit. Issue 4 (December 2016) - Manias, Elizabeth; Geddes, Fiona; Della, Phillip; Jones, Dorothy; Watson, Bernadette; Stewart-Wynne, Edward
Summary: Patients requiring inter-hospital air transport across large geographical spaces are at significant risk of adverse outcomes. The aims of this study were to examine the characteristics of clinical handover conducted by telephone and subsequently transcribed in medical records during the inter-hospital transfer of rural patients, and to identify any deficits of this telephone clinical handover. A retrospective audit was conducted of transcribed telephone handovers ('patient expect' calls) occurring with inter-hospital transfers from two rural hospitals to a metropolitan tertiary hospital of all rural patients ( n  = 127) between January and June 2012. Patient transport between various sites occurred through the Royal Flying Doctor Service. For these hospitals, patient expect calls constituted the only handover record for clinicians during the time of patient transport. Information on patient identification stickers relating to patients' age or gender did not always correspond with details collected during patient expect calls. The name of a clinician at the receiving hospital authorising the transfer was provided in 14 calls (11.1%). It was difficult to determine who made and received calls, and who accepted responsibility for patients at the receiving site. Deterioration in a patient's condition was made in three calls. Actions to be taken after patients' arrival were included in 24 (19%) calls. Planning was restricted to identifying who to contact to review instructions. Inconsistent and overuse of abbreviations was likely to have affected the ability to accurately read back patient information. Crucial information was missing from calls, which may have contributed to delayed and inappropriate delivery of care.